2017
DOI: 10.7717/peerj.3867
|View full text |Cite
|
Sign up to set email alerts
|

Development and validation of near-infrared spectroscopy for the prediction of forage quality parameters in Lolium multiflorum

Abstract: Italian ryegrass (Lolium multiflorum) is an important cool-season, annual forage crop for the grassland rotation system in Southern China. The primary aim of breeding programs is always to seek to improve forage quality in the animal productivity system; however, it is time- and labor-consuming when analyzed excessive large number of samples. The main objectives of this study were to construct near-infrared reflectance spectroscopy (NIRS) models to predict the forage chemistry quality of Italian ryegrass inclu… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
2
1
1
1

Citation Types

4
39
2

Year Published

2019
2019
2024
2024

Publication Types

Select...
8

Relationship

0
8

Authors

Journals

citations
Cited by 47 publications
(45 citation statements)
references
References 53 publications
4
39
2
Order By: Relevance
“…The SWIR region is also widely used for CP and NDF estimation in forage [6,7,13,29,76,78,[92][93][94][95][96][97][98]. Our results are in agreement with other studies that have also reported the importance of the SWIR region, and specifically for the wavelengths of 2202 nm (CP in rapeseed, R 2 = 0.98 [99] and 2204 nm (NDF in forage, R 2 = 0.97 [16].…”
Section: Discussionsupporting
confidence: 91%
“…The SWIR region is also widely used for CP and NDF estimation in forage [6,7,13,29,76,78,[92][93][94][95][96][97][98]. Our results are in agreement with other studies that have also reported the importance of the SWIR region, and specifically for the wavelengths of 2202 nm (CP in rapeseed, R 2 = 0.98 [99] and 2204 nm (NDF in forage, R 2 = 0.97 [16].…”
Section: Discussionsupporting
confidence: 91%
“…In comparison to ADF, the NDF concentration of tepary samples were less accurately predicted by all three techniques (Table 3). Similar differences between prediction accuracy of ADF and NDF were also noticed for guar in this study, and also reported earlier in NIRS studies involving Brassica napus [26], Lolium multiflorum [11], and Oryza sativa [27]. Though PLS performed better at predicting IVTD in tepary bean compared to other two, all three techniques resulted in relatively low prediction accuracy with R 2 cv and R 2 v ranging between 0.75-0.79 and 0.75-0.88, respectively.…”
Section: Parametersupporting
confidence: 92%
“…The method of applying NIRS to predict forage quality involves analyzing a particular forage with both traditional lab analysis and NIRS, and then developing a predictive equation by pairing the information in a calibration dataset ( Figure 1). The NIRS has been widely used in forage quality predictions of crops including alfalfa (Medicago sativa) [9], maize (Zea mays) [10], ryegrass (Lolium multiflorum) [11], tall fescue (Festuca arundinacea) [12], and other species. However, the technique has been underutilized to provide predictions of forage quality for many warm-season legumes.…”
Section: Introductionmentioning
confidence: 99%
“…Forage can be dried or oven-dried and afterwards ground to 1 mm (Bezada et al, 2017;Simeone et al, 2015;Andueza et al, 2016;Molano et al, 2016;Durmic et al, 2017;Ullmann et al, 2017;Parrini et al, 2018) or 2 mm (Zhang et al, 2017). This is done for the sake of standardization, especially because the quality of the calibration can be increased with sample preparation and measurement standardization (Reddersen et al, 2013).…”
Section: Forage Preparationmentioning
confidence: 99%